Problems of genetic diagnosis: serological markers in the prognosis of the development of human speed abilities - Serhiyenko Leonid Prokopovich; Lyshevska Valentina Mikhajlovna (Kharkov National Pedagogical University, 2011)
The article deals with the study of correlation between blood groups system AB0 and Rh with the peculiarities of the development of human speed abilities. Complex of genetic markers is defined. It is possible to use this complex in the individual prognosis of the development of human motor abilities. With 0(I) and A(II) blood groups and Rh+ have a high inclination to the physical development. Better identify trends in the phenotypic expression of high-speed abilities in people with 0(I) and A(II) blood groups in comparison with people with the AB(IV) and B(III) blood group. The pattern of decreasing susceptibility to the development of high-speed abilities as follows: 0(I)>A(II)>B(III)>AB (IV). It is established that a complex system of genetic markers AB0 and Rh blood has no gender differences.